Trace element profiles in pregnant women's sera and umbilical cord sera and influencing factors: Repeated measurements. (March 2019) - Liang, Chun-mei; Wu, Xiao-yan; Huang, Kun; Yan, Shuang-qin; Li, Zhi-juan; Xia, Xun; Pan, Wei-jun; Sheng, Jie; Tao, Yi-ran; Xiang, Hai-yun; Hao, Jia-hu; Wang, Qu-nan; et al.
Abstract: In utero exposure to toxic heavy metals and deficient or excessive essential trace elements during pregnancy may have adverse effects on pregnant women and their offsprings, which are of great concern. The objective of the present study was to characterize serum concentrations of multiple trace elements at multiple time points during pregnancy in Chinese women. Three thousand four hundred and sixteen pregnant women in total were included from MABC (Ma'anshan Birth Cohort) study. Fasting sera in the morning and questionnaires were obtained at three separate follow-up visits. Nineteen trace elements from serum samples were analyzed, including aluminum (Al), vanadium (V), chromium (Cr), manganese (Mn), iron (Fe), cobalt (Co), nickel (Ni), copper (Cu), zinc (Zn), arsenic (As), selenium (Se), cadmium (Cd), barium (Ba), thallium (Tl), lead (Pb), calcium (Ca), magnesium (Mg), mercury (Hg) and molybdenum (Mo). The total detection rates for most elements were 100% rather than Ni (99.98%), As (99.97%), Cd (99.6%), Ba (99.9%), Pb (99.8%), Hg (99.8%). The concentration distributions of 19 elements varied vastly. Median concentrations for all trace elements ranged from 38.5 ng/L to 102.9 mg/L. The moderate interclass correlation coefficients (ICCs) were observed for Co, Cu, Se and Hg, ranging from 0.40 to 0.62; the lower ICCs, ranging from 0.13 to 0.32 were for Fe, Zn, Cd, Ba, Tl, Mg and Mo. The intraclass correlation effects were not observed for the remaining elements, such as Al, V, Cr, Mn, Ni, As and Pb. The concentrations of each element between three time points were significantly different; significant differences were also found between any two time points except for Ni, Cd and Mo. Many factors could affect the levels of trace elements, and a very important factor of them was season. Consequently, a single measurement of elements in sera seems not enough to describe exposure levels throughout pregnancy; additionally, season affected exposure levels of trace elements with moderate ICCs showed certain regularity. Future analyses should take sampling seasons into consideration carefully. Highlights: A first cohort study investigated profiles of multiple trace elements with repeated measurements. Demonstrated mild to moderate temporal stabilities for these elements throughout pregnancy. Most element levels were related with sampling seasons and other factors. Factors affected exposure levels of trace elements with moderate ICCs showed certain regularity.